Pendidikan karakter dalam Islam: Solusi untuk dekadensi moral generasi muda - Abdul Aziz, Hamdan; Shajaratuddar, Shajaratuddar; Handrianto, Budi (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2023)
This research aims to understand character education in Islam as a solution to the moral decadence of the younger generation. Through a literature study approach and content analysis, this research explores various related literature and sources to gain a comprehensive understanding of the importance of instilling morals in the education process. The results show that character education in Islam plays a very important role in shaping good morals in the younger generation. Teachers as educators must be role models in their behaviour and morals, while students need to accept and practice the moral values taught. Through strong character education, the younger generation can grow into individuals who are responsible, honest, fair, and have a positive attitude towards the environment and others. This research provides a deeper understanding of the importance of character education in Islam as an effort to overcome the moral decadence of the younger generation. The implication of this research is the need for greater attention to character education in the education system and curriculum development that includes moral values as an integral part of learning. Abstrak         Penelitian ini bertujuan untuk memahami pendidikan karakter dalam Islam sebagai solusi terhadap dekadensi moral generasi muda. Melalui pendekatan studi pustaka dan analisis isi, penelitian ini menggali berbagai literatur dan sumber terkait untuk mendapatkan pemahaman yang komprehensif tentang pentingnya penanaman akhlak dalam proses pendidikan. Hasil penelitian menunjukkan bahwa pendidikan karakter dalam Islam memainkan peran yang sangat penting dalam membentuk akhlak yang baik pada generasi muda. Guru sebagai pendidik harus menjadi contoh teladan dalam perilaku dan akhlaknya, sementara murid perlu menerima dan mengamalkan nilai-nilai akhlak yang diajarkan. Melalui pendidikan karakter yang kuat, generasi muda dapat tumbuh menjadi individu yang bertanggung jawab, jujur, adil, dan memiliki sikap positif terhadap lingkungan dan sesama. Penelitian ini memberikan pemahaman yang lebih mendalam tentang pentingnya pendidikan karakter dalam Islam sebagai upaya untuk mengatasi dekadensi moral generasi muda. Implikasi penelitian ini adalah perlunya perhatian yang lebih besar terhadap pendidikan karakter dalam sistem pendidikan dan pengembangan kurikulum yang memasukkan nilai-nilai akhlak sebagai bagian integral dari pembelajaran.